2018
DOI: 10.1002/ange.201802881
|View full text |Cite
|
Sign up to set email alerts
|

A Nanohelicoidal Nematic Liquid Crystal Formed by a Non‐Linear Duplexed Hexamer

Abstract: The twist-bend modulated nematic liquid-crystal phase exhibits formation of an anometre-scale helical pitchi n afluid and spontaneous breaking of mirror symmetry,leading to aquasi-fluid state composed of chiral domains despite being composed of achiral materials.T his phase was only observed for materials with two or more mesogenic units,the manner of attachment between whichi sa lways linear.N on-linear oligomers with aH -shaped hexamesogen are nowf ound to exhibit both nematic and twist-bend modulated nemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Recently, duplex formation has been proposed [38,41,42]. We note that for this system at low concentrations of CBC3CB (roughly 12 mol%) only one in five duplexes would contain species promoting helicoidal structure formation, this would indicate that either CBC3CB is very efficient as a dopant or alternatively disfavours the concept of duplexes.…”
Section: In the Esi)mentioning
confidence: 77%
“…Recently, duplex formation has been proposed [38,41,42]. We note that for this system at low concentrations of CBC3CB (roughly 12 mol%) only one in five duplexes would contain species promoting helicoidal structure formation, this would indicate that either CBC3CB is very efficient as a dopant or alternatively disfavours the concept of duplexes.…”
Section: In the Esi)mentioning
confidence: 77%
“…[16] Ramou et al reported that the N TB phase can be induced in mixtures of conventionaln ematic and nonmesogenic dimers. [17] Besides liquid-crystal dimers, the N TB phase has also been observedi nb ent-core molecules, [5,[18][19][20] oligomers, [21][22][23][24][25] and polymers. [3,4,26] Although the majority of twist-bend nematogens developeds of ar are achiral,t here have been af ew reports on formation of the N TB phase based on chiral bentshaped molecules,i nw hicht he chirality is located in the mesogenic-arm core, [27,28] terminal chain, [29] or spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CB7CB is, on average, a bent molecule, and the observation of the N TB phase may be accounted for within the framework of Dozov's prediction [5]. Indeed, the vast majority of twist-bend nematogens may be described as odd-membered liquid crystal dimers (see for example [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]) although other structures including hydrogen-bonded materials [29][30][31][32][33], higher oligomers [34][35][36][37][38][39][40], polymers [41] and semi-rigid bent-core materials [42] have also been shown to exhibit the N TB phase. In each of these classes of material, however, it is widely accepted that the stability of the N TB phase is strongly dependent on molecular shape, and specifically, molecular curvature.…”
Section: Introductionmentioning
confidence: 99%